TMS-fMRI to uncover cognition and behavior in healthy individuals - Siebner, H.R. (Clinical neurophysiology, 2016)
A wide range of functional brain mapping techniques is widely available such as EEG, functional magnetic resonance imaging (fMRI), and PET. While these methods provide insights into spatiotemporal brain activation, they are merely correlational and therefore, no causal inferences can be made regarding human brain function. The combination of transcranial magnetic stimulation (TMS) with fMRI provides a powerful means of “causal mapping” of human brain networks. TMS during fMRI (online approach) can be used to test how focal cortex stimulation acutely modifies the activity and connectivity in the stimulated neuronal circuits. TMS and neuroimaging can also be separated in time (offline approach). Conditioning repetitive TMS before neuroimaging can give valuable insights into the causal dynamics of functional brain networks. Task-related fMRI before a TMS session can guide the location and timing of TMS.